Drawing the field of mathematics: Application of the concepts of pierre bourdieu in mathematical education - Farias, Jose Vilani de; Vilela, Denise Silva (FCL-UNESP Laboratório Editorial, 2020)
From Pierre Bourdieu's sociological theory and the research in Mathematical Education, it is presented in this article an interpretation of mathematics as a field: with its laws, agents, capitals, disputes, tastes and distinctions. Our goal was to design the field of mathematics, from the analysis of a professional mathematics Master's Program in national network (Profmat). This program was conceived and implemented by the Sociedade Brasileira de Matemática ( Brazilian Mathematics Society) and by Instituto de Matemática Pura e Aplicada( Institute of Pure and Applied Mathematics), institutions recognized as developing high-level research in mathematics, but not recognized in the context of research in teacher training. The sociological investigation carried out by elaborating the notion of field, allowed an understanding of Profmat as a strategy for valuing a mathematical practice and an understanding of mathematics as a hierarchical space of agents in dispute for the right to define what is mathematics and who has enough distinction to define it.